Strategi Komunikasi Kepala Madrasah dalam Membina Akhlakul Karimah Peserta Didik - Nurudin, Muhammad; Ramli, Ramli; Qadaruddin, Muhammad; Nurkidam, A.; Iskandar, Iskandar (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The main problem is how the communication strategy in fostering students' akhlakul karimah. The research uses qualitative methods and theories of persuasive theory and behaviorism. The paradigm of this research is naturalism; the source of data is the head of the madrasa, teachers, education personnel and students (primary data) and documents of fostering akhlakul karimah MTs Ma'arif Pinrang (secondary data); the research instrument is the researcher himself and is assisted through data collection tools, namely observation guideline sheets, interview guidelines, digital cameras and tape recorders; data collection techniques are participatory observation, in-depth interviews, and documentation; and testing the validity of the research results, namely credibility, transferadibility, and confirmability. The results showed: (1) The head of the madrasa in fostering the morals of students applies persuasive strategies by using assumption, integration, reward and arrangement techniques. Meanwhile, in applying the behaviorism strategy using 3 steps, namely stimulus, process and response. In the stimulus stage, the madrasah principal sets rules regarding the obligation to be morally good. At the communication process stage, the madrasah principal uses interpersonal communication of the redundancy, verbal and non-verbal communication types. The form of coaching uses exemplary coaching, habituation, advice, and punishment. From the entire series of application of communication strategies, it shows a response / improvement in the morals of students in terms of religiosity (religion), discipline, responsibility, peace-loving, environmental care and social care. (2) Supporting factors for communication are closeness, mutual respect, and feedback by students. While the inhibiting factors are voice intonation when communicating, speech speed or tempo and vocabulary due to ethnic differences.